The Government Use and Compulsory License: Questioning the Patent Application of Drug and Covid-19 Vaccines - Rohaini, Rohaini; Dwiatin, Lindati; Eka R, Dianne (Jambe Law Journal, 2022)
The pandemic of Covid-19 and the urgent global needs to immediately obtain an effective drugs or Covid-19 vaccines have impacted the competition of pharmaceutical inventions and the patent registration of drugs or Covid-19 vaccines. However, this circumstance raise pro and cons. There is concern that there will be a conflict between the economic interests of the patent holder and public interest. Patent rights granted to the inventors or pharmaceutical companies has caused difficulties of the State to provide medicines or vaccines to the public since the production and distribution of it has been fully under their control. In this regard, the government use and compulsory license mechanisms are believed to be the most likely policies by the Government for balancing the use of exclusive rights and the economic interests of patent holders. It allow the Government to access and exploit patented inventions without prior consent from the patent holder, but at the same time the patent holder still get the protection and their rights.